2015
DOI: 10.1055/s-0034-1393731
|View full text |Cite|
|
Sign up to set email alerts
|

Computer-Assisted Three-Dimensional Planning for Orbital Decompression

Abstract: Thyroid-associated orbitopathy is the most common cause of unilateral or bilateral proptosis in adults. A mainstay of surgical treatment is orbital decompression utilizing osteotomies to increase the size of the affected bony orbit to accommodate the larger soft tissue volume. Over the past several decades, numerous approaches have been described for orbital decompression. However, given the intricate osseous and soft tissue anatomy within the orbit, orbital decompression is a potentially hazardous interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
(99 reference statements)
0
12
0
Order By: Relevance
“…One reason is probably the limitations of two-dimensional measurements: Curved orbital walls are measured with straight measurements [50]. Newer, more complex techniques in three-dimensional scans are able to map the real orbit and not only an approximation [28, 36, 37, 51]. However, even they might not be sufficient, since the prolapse of orbital tissue during decompression surgery shows great individual variety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason is probably the limitations of two-dimensional measurements: Curved orbital walls are measured with straight measurements [50]. Newer, more complex techniques in three-dimensional scans are able to map the real orbit and not only an approximation [28, 36, 37, 51]. However, even they might not be sufficient, since the prolapse of orbital tissue during decompression surgery shows great individual variety.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, single-center experiences with different three-dimensional planning approaches have been described. However, there has been no data on the efficacy of these techniques yet [36, 37].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, this technology is currently accessible to clinicians and researchers. Compared to MRI, CT is more widely used by surgeons due to its ability to precisely reconstruct data using better threshold separation . The advantage of MRI, however, lies in the avoidance of radiation exposure, which is greatly appreciated in oriental culture.…”
Section: Discussionmentioning
confidence: 99%
“…Intraorbital hemorrhage can occur with orbital decompression and can lead to vision loss from orbital compartment syndrome. Some have suggested placing a drain in the orbit as a method of prevention, but in this study only 17.8% of surgeons reported that they routinely do so [14, 21]. Overnight admission for observation can be considered, and in our survey 44.4% of surgeons stated that they routinely admit patients following decompression surgery.…”
Section: Discussionmentioning
confidence: 68%
“…Stereotactic navigation has been described for orbital decompression surgery as a method allowing the precise removal of the maximum amount of bone during surgery while using a smaller incision, particularly when identifying the safe limits of bony lateral decompression [20, 21]. However, the use of this technology may be limited by the learning curve involved as well as the high cost of the equipment [20].…”
Section: Discussionmentioning
confidence: 99%